A Rare Stapes Abnormality - Hala Kanona; Jagdeep Singh Virk; Gaurav Kumar; Sanjiv Chawda; Sherif Khalil (Case Reports in Otolaryngology)
The aim of this study is to increase awareness of rare presentations, diagnostic difficulties alongside management of conductive hearing loss and ossicular abnormalities. We report the case of a 13-year-old female reporting progressive left-sided hearing loss and high resolution computed tomography was initially reported as normal. Exploratory tympanotomy revealed an absent stapedius tendon and lack of connection between the stapes superstructure and footplate. The footplate was fixed. Stapedotomy and stapes prosthesis insertion resulted in closure of the air-bone gap by 50 dB. A review of world literature was performed using MedLine. Middle ear ossicular discontinuity can result in significant conductive hearing loss. This can be managed effectively with surgery to help restore hearing. However, some patients may not be suitable or decline surgical intervention and can be managed safely conservatively.